Keywords:informationInformationQ Pengaruh kualitas informasi terhadap keputusan pembelian online produk fashion pada Shopee (Study Pada Mahasiswa Politeknik Jurusan Administarsi Bisnis) - Lado, Ririn Yuniar (Bisman - Jurnal Bisnis & Manajemen, 2019)
The Influence of Information Quality to The Purchasing Decision of Fashion Product in Shopee Application the case study in Business Administration Department”. The problem in this research was how the information quality influenced the purchasing decision. The population were the students of Business Administration Department on the last semester as many as 145 students who used Shopee application with the samples of 60 people. The data was obtained through distributing the questionnaires, observation and interview. The technique used simple random sampling technique. The data used primary data and secondary data, and data analysis used simple linear regression analysis formula. The analysis result used SPSS V.16 program showed that determination coefficient table showed that R square was 0,523, it means the the influence of information quality to purchasing decision as many as 52,3%. And based on the t test obtained t count as many as 3,264 with the significant level as many as 0,000 less than Cronbach’s Alpha (a) (0,000 < 3,264), it means that information quality is one of the factors that really influences the purchasing decision of fashion product in Shopee application